Analysis of the regime for micro-enterprises - López Gómez, Kerly; Mera Bozano, Fabian; Gaibor González, Israel (mktDESCUBRE; Vol 1 No Especial (2021): Special Edition 4th International Scientific Congress of Administrative and Financial Sciences FADE 2020DO - 10.36779/mktdescubre.v1iEspecial.569, 2021)
Microenterprises require State participation for their permanence, so that fiscal policy fulfills its role of promoting productivity and employment, through benefits and tax incentives that promote their creation, this is how the State has promoted the law of Tax Simplification and Progressivity, including a regime for micro-enterprises. The purpose of this research is to know the economic sector with the highest income and relate the values declared as taxable income and tax caused, in order to determine the impact on collection. The research approach is quantitative in nature, because statistical techniques were used in the analysis of the data, the same ones that were collected through the Internal Revenue Service, to generalize the results from the economic returns generated by micro-enterprises It is also a documentary bibliographic research. The conclusion reached in this study is that micro-enterprises in Ecuador represent around 53% of active taxpayers, in addition the tax caused by fiscal year 2020 compared to 2019 will have a variation of 69%, paying a higher tax in the year 2020.